Intelligent prosthetic hips and knees: from actuation to perception and control - Wang, Xiaoming; Li, Yuanhua; Yu, Hongliu (Frontiers in Neuroscience, 2026)
Intelligent prosthetic hips and knees represent a critical advancement in restoring natural gait and mobility for lower-limb amputees, particularly those with high-level amputations such as hip disarticulation. This systematic review examines recent progress in three fundamental aspects of intelligent prosthetic technology: actuation, perception, and control. In terms of actuation, the review highlights the limitations of passive and active prostheses and discusses emerging hybrid active-passive mechanisms that aim to replicate the natural, biarticular muscle-driven energy transfer in human gait. The perception section addresses current methodologies for recognizing human motion intentions through mechanical, bioelectric, biomechanical, and external environmental signals, underscoring the challenges of stability, latency, and interference inherent in existing approaches. Regarding control strategies, the paper categorizes intelligent control into torque compensation, motion following, and direct intention control, outlining the strengths and limitations of each method. The review identifies critical technological bottlenecks, including signal interference, limited adaptability to dynamic environments, and the absence of effective real-time intention recognition methods. The paper concludes by suggesting future directions in the development of hybrid actuation and advanced perception-control integration, essential for improving the usability and efficacy of intelligent prosthetic hips and knees, ultimately enhancing mobility and quality of life for amputees.